1997
DOI: 10.1111/j.1749-6632.1997.tb48481.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials in Dementia with Propentofyllinea

Abstract: The mode of action of propentofylline (a xanthine derivative) suggested that it would have beneficial effects in patients with Alzheimer's disease or vascular dementia. In four double-blind, placebo-controlled, randomized studies, 901 patients with mild to moderate Alzheimer's disease and 359 patients with mild to moderate vascular dementia were treated for up to 12 months (daily dose of propentofylline: 3 x 300 mg taken 1 hr before food). Patients were assessed at regular intervals for efficacy and safety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…For example, AD and VaD share features involving cerebral hypoperfusion, white matter changes, [165][166][167] The similarities of the clinical presentation, pathophysiology, and rate of cognitive decline between AD and VaD have led to the development of treatments that appear useful to both conditions at the level where risk factors are discovered or during the disease process. 109,110,177,190 -192 For this reason, several pharmaceutical companies have targeted both dementias using a common drug application, 110,111,191 with the rationale that central cholinergic mechanisms are impaired in both AD and VaD. 192 However, it is also possible that cholinesterase inhibitors have another action aside from increasing acetylcholine stores: that of improving CBF modestly and transiently by their vasodilating innervation derived from the nucleus basalis of Meynert.…”
Section: Ad-vad Correlatesmentioning
confidence: 99%
“…For example, AD and VaD share features involving cerebral hypoperfusion, white matter changes, [165][166][167] The similarities of the clinical presentation, pathophysiology, and rate of cognitive decline between AD and VaD have led to the development of treatments that appear useful to both conditions at the level where risk factors are discovered or during the disease process. 109,110,177,190 -192 For this reason, several pharmaceutical companies have targeted both dementias using a common drug application, 110,111,191 with the rationale that central cholinergic mechanisms are impaired in both AD and VaD. 192 However, it is also possible that cholinesterase inhibitors have another action aside from increasing acetylcholine stores: that of improving CBF modestly and transiently by their vasodilating innervation derived from the nucleus basalis of Meynert.…”
Section: Ad-vad Correlatesmentioning
confidence: 99%
“…For example, in a rodent model of stroke in which there is unilateral damage to the sensorimotor cortex, treatment with inosine improved functional recovery by a mechanism that involved induction of genes encoding proteins involved in axon growth (Zai et al, 2009). The xanthine derivative propentofylline was reported to be effective in preserving cognitive function in patients with Alzheimer disease (Kittner et al, 1997), although whether its efficacy is the result of actions on ryanodine receptors, phosphodiesterases, or another mechanism is unknown. It is noteworthy that recent findings suggest that individuals with relatively higher plasma uric acid levels are at reduced risk of developing Alzheimer disease (Irizarry et al, 2009), and uric acid protected cultured neurons from being killed by amyloid ␤-peptide (Guo et al, 1999).…”
Section: Pharmacology Of Endoplasmic Reticulum Ca 2؉ -Handling Smentioning
confidence: 99%
“…These studies suggested that the treatment may be beneficial but the differences between patients receiving treatment and those given the placebo were small and often not statistically significant. Another drug which may be effective is propentofylline [24][25][26], which strongly inhibits the potentially neurotoxic actions of activated microglia (free radical formation and transformation into brain macrophages). This drug may inhibit the progressive neurodegenerative process in dementia; however, randomized, double-blind placebocontrolled trials are required to establish whether this drug is effective.…”
Section: Curative Treatmentmentioning
confidence: 99%